Effect of music therapy on language skills in children with specific language impairment: A systematic review - Wanicharoen, Natwipa; Boonrod, Vich (Journal of Associated Medical Sciences, 2023)
Background: Specific language impairment (SLI) delays language development without any neurological damage or disease. This impairment extends to nonlinguistic tasks, such as music perception skills. In recent years, speech-language pathologists (SLPs) and music therapists (MTs) have collaborated to develop and improve approaches for children with communication disorders (CDs), including global developmental delay (GDD), SLI, mild developmental delay (DD), and the risk of developing reading difficulties, by integrating music therapy (MT) and speech therapy (ST). MT could be considered as one of the alternative methods offered to children with SLI to enhance their language skills. Objectives: The purpose of this study was to investigate the effectiveness of MT interventions on language skills in children with SLI and to investigate the characteristics of other intervention features in these studies, such as interventionists, intervention, settings, session type, and music methods. Materials and methods: The study was a systematic review conducted within the framework of the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA). The quality of the research results was assessed using the critical appraisal tools provided by the Joanna Briggs Institute (JBI). Results: Two studies met the inclusion criteria and were included in this systematic review. The two main types of MT employed were song cues and creative music therapy based on the Nordoff-Robbins approach. Current evidence suggests that music therapy improves components of language, including phonology, syntax, morphology, and other aspects of speech development, such as understanding sentences and memory for sentences, in children with SLI. Conclusion: MT can be a valuable and effective intervention for children with SLI. The introduction of transdisciplinary programs that integrate MT and ST could be recommended. However, MT training courses are required for SLPs.